Manajemen Komunikasi dalam Situasi Krisis: Studi Kasus “Mishandled Baggage” di JAS Airport Services di Bandara Internasional Juanda Surabaya - Ramadhan, Muhammad Farhan; Indriastuti, Yudiana; Arviani, Heidy (LPPM Institut Pendidikan Nusantara Global, 2025)
The mishandled baggage incident at JAS Airport Services reflects the weakness of communication management within the complex and dynamic environment of ground handling operations. This study aims to analyze communication management strategies in responding to crises and evaluate their effectiveness in maintaining service quality. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, field observations, and documentation. The findings reveal that internal communication failures—ranging from the lack of enforcement of communication objectives to the absence of regular evaluations—were the root causes of the crisis. As a result, JAS not only suffered financial losses but also faced reputational risks with international airlines as key clients. Linked to the SERVQUAL model, the incident affected several dimensions, including reliability, responsiveness, assurance, and empathy. This study highlights that communication must become an organizational culture, not merely an administrative procedure, in order to maintain service quality and prevent recurring crises.